Analisis Strategi Sistem Teknologi Informasi Dengan Pendekatan Analisis Swot Pada Cafe D 'Sruput Di Kota Padang - Fauzan Abdilla; Nila Sovianti; Shelbila Adita; Sirotil Hasanah; Ramdani Bayu Putra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Strategic management is an important approach in managing an organization to achieve its long-term goals. This involves formulating the vision, mission, and goals of the organization, as well as developing and implementing strategic plans to achieve these goals.SWOT analysis is a tool used in strategic management to identify internal and external factors that affect the performance of an organization or a project.SWOT analysis assists organizations in formulating strategies by considering internal strengths and weaknesses, as well as existing external opportunities and threats. The application of information technology systems will be beneficial if the application is in accordance with the goals, vision and mission of the organization by establishing business strategies and information technology systems strategies related to SWOT Analysis.The research method used is the SWOT Analysis Technique including IFE, EFE, and TOWS. The IFE matrix shows that Cafe D'Sruput has strong organizational characteristics internally while the EFE matrix shows the weaknesses of cafe D'Sruput, so that cafe D'Sruput can carry out market development, product development and innovate in developing business at cafe D' Slurp.